2021
DOI: 10.1021/acsami.1c03757
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High VOC Organic Solar Cells with a Non-Halogenated Solvent and the Effect of Substituted Groups for “Same-A-Strategy” Material Combinations

Abstract: We report a class of high-voltage organic solar cells (OSCs) processed by the environmentally friendly solvent tetrahydrofuran (THF), where four benzotriazole (BTA)-based p-type polymers (PE31, PE32, PE33, and J52-Cl) and a BTA-based small molecule BTA5 are applied as p-type and n-type materials, respectively, according to “Same-A-Strategy” (SAS). The single-junction OSCs based on all four material blends exhibit a high open-circuit voltage (V OC) above 1.10 V. We systematically study the impact of the three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…In these samples, strong PL quenching of the blend compared to the neat was observed; indicating domain size compatible with exciton diffusion length [48]. Similar observation was reported for the study of benzotriazole (BTA)-based p-type polymers (PE31, PE32, PE33, and J52-Cl) when blended with a BTAbased small molecule BTA5 using THF [47]. It was shown that PE31:BTA5 exhibited the highest PCE of 10.08%, which correlated with the highest PL quenching, whilst the other blends had reduced PL quenching; insinuating less optimum morphology of domain size.…”
Section: Photoluminescence Assay Of Exciton Dissociationsupporting
confidence: 82%
See 1 more Smart Citation
“…In these samples, strong PL quenching of the blend compared to the neat was observed; indicating domain size compatible with exciton diffusion length [48]. Similar observation was reported for the study of benzotriazole (BTA)-based p-type polymers (PE31, PE32, PE33, and J52-Cl) when blended with a BTAbased small molecule BTA5 using THF [47]. It was shown that PE31:BTA5 exhibited the highest PCE of 10.08%, which correlated with the highest PL quenching, whilst the other blends had reduced PL quenching; insinuating less optimum morphology of domain size.…”
Section: Photoluminescence Assay Of Exciton Dissociationsupporting
confidence: 82%
“…Such a result is ascribed to a better packing of the compounds leading to a good level of intermolecular organization. In contrast, due to the weak crystallinity of the methoxy-substituted polymer PE32, the resulting device shows the lowest PCE of 7.40% [47]. All polymer solar cells were prepared by Sunsun et al using a perylenediimide (PDI)-bithiophene-based polymer acceptor PPDIODT, and PBDT-TS1 as polymer donor.…”
Section: Organic Semiconductors Design Towards Green Solvent Processing Oscsmentioning
confidence: 99%
“…[28][29][30][31][32] Among different types of halogenations, fluorination is one of the most important molecular design strategies to further improve the performance of PSCs. [33][34][35][36][37][38][39][40][41] First, due to the strong electron-withdrawing effect with a very small size, the introduction of fluorine atom is beneficial to simultaneously downshift the frontier molecular orbitals and to reduce the optical bandgap without using a large π-conjugated system. Second, the formation of noncovalent interactions, such as F•••H and F•••S, can effectively reduce the intermolecular π-π stacking distance, leading to improved charge transport properties of the resulting NFAs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been increased interest in these heterocycles for their use in organic materials consisting of π-conjugated electron-donor and electron-acceptor polymers (i.e., n-type and p-type materials, respectively). These conjugated polymers show promise for use in organic photovoltaics, organic light-emitting diodes, and high-voltage solar cells. ,,,, Recently, a great deal of attention has focused on the N2-benzotriazole moiety as an important molecular linker in such polymers because of its significant electron-withdrawing properties, which make it a valuable substituent in p-type materials. , Scheme (upper) contains an example of a monomeric unit containing the N2-benzotriazole moiety, which is considered to be an electron acceptor in this polymer . Notably, recent studies have demonstrated that the N2-benzotriazole moiety is versatile and can be incorporated into both electron-accepting and electron-donating polymeric materials when appropriate functional groups are attached …”
Section: Introductionmentioning
confidence: 99%
“…10−18 These conjugated polymers show promise for use in organic photovoltaics, organic light-emitting diodes, and high-voltage solar cells. 12,14,15,17,18 Recently, a great deal of attention has focused on the N2-benzotriazole moiety as an important molecular linker in such polymers because of its significant electron-withdrawing properties, which make it a valuable substituent in p-type materials. 11,12 Scheme 1 (upper) contains an example of a monomeric unit containing the N2benzotriazole moiety, which is considered to be an electron acceptor in this polymer.…”
mentioning
confidence: 99%